Comparative Study of Metformin Hydrochloride Tablets in Argentina - Brevedan, Marta Ingrid Victoria (2024)
Metformin, a class III drug in the Biopharmaceutics Classification System, is an orally administered drug used to lower blood glucose concentrations in patients with non-insulin-dependent diabetes mellitus. Different quality parameters were assayed for Metformin immediate-release tablets (500 mg), obtained from pharmacies in Argentina, in order to compare the commercially available samples, ascertain pharmaceutical equivalence and interchangeability. Label evaluation, hardness, friability, disintegration time, uniformity of dosage units, assay and in vitro dissolution were assessed in accordance with the Argentine Pharmacopeia requirements. Mathematical and statistical comparative models were used to characterize the dissolution profiles obtained under physiological conditions. All evaluated products fulfilled the pharmaceutical equivalence criteria. Nevertheless, the biowaiver scheme could not be applied since not all formulations, including the reference product, fulfilled the very rapidly dissolving criterion applicable to Class III drug products.